EVALUATION OF DRIVE-THRU PHARMACY SERVICE ASSESSED THROUGH THE IMPACT OF DRUG INFORMATION SERVICES ON ADHERENCE LEVELS AND SATISFACTION OF HYPERTENSIVE PATIENTS DURING THE COVID-19 PANDEMIC - Andria, Resta
Drive-thru pharmacy service was developed to overcome the challenges of pharmaceutical services during COVID-19 pandemic. However, until now there has been no evaluation about the level of satisfaction and adherence of patients who use drive-thru pharmacy service, especially patients with chronic diseases such as hypertension. Hence, this study aimed to evaluate the drive-thru service in terms of the level of satisfaction and patient adherence in taking medicine for Hypertension treatment. This study was a descriptive observational study with a prospective cross-sectional design performed by providing a validated standard questionnaire to hypertensive patients who were prescribed anti-hypertensive medication, during January – March 2022. The sampling technique used nonprobability consecutive sampling. There were 110 patients were included and grouped into drive-thru (55 patients) and non-drive thru (55 patients) based on the service they received. The research instrument used was Morisky Medication Adherence Scale (MMAS-8) and Servqual. The level of satisfaction was analyzed using GAP analysis, Consumer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The respondents were dominated by male (50,91%), aged >46 years (67.27%), with high school education (35.54%) and those who work as civil servants/for state-owned companies (BUMN) (25.45%). The level of adherence of patients who used drive-thru were 30.90%, and non drive-thru were 54.54%. The level of adherence was significantly correlated (p-value <0.05) with patients demographic. The GAP analysis showed that for both groups the lowest GAP was found in Empathy ( drive-thru: -0.54, non-drive thru -0.50). The highest GAP for drive-thru were found in reliability (-0.72) and responsiveness (-0.72), while for non-drive-thru was in reliability (-0.79). There was no significant difference level of patient satisfaction between drive-thru services and non drivethru services used the Whitney significance test <0.47. The CSI values for Non Drive-thru (86,42%) and Drive-thru (82.22%) were in the “very satisfied” category. Based on the IPA Cartesian diagram, the attributes included in quadrant I (focus improvement) for drive-thru service were empathy and assurance dimensions, while for the non-drive-thru service were reliability, assurance and empathy dimensions.